Iowa RBA, October 7, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for October 7, 1996. Highlights of the update include sightings of two Sabine's Gulls in northwest Iowa and the early appearance of a Thayer's Gull in the southeast part of the state. Also of note were the number of migrants moving into the state, including Sparrows, Kinglets, and late Warblers. Also included are handwritten notes for the next week's update with sightings of a female Surf Scoter and American Pipits. Epson - sheet feed/flatbed